MEAT PHYSICAL AND SENSORIC QUALITY OF BRAHMAN CROSS CATTLE FED PINEAPPLE WASTE AS FIBER SOURCE - Wahyuni, Dewi; Priyanto, Rudy; Nurani, Henny (Universitas Djuanda, 2018)
Meat quality represents meat properties known by consumers and affects their acceptance. Feed is one of the factors affecting meat quality. Utilization of pineapple waste as a fiber source in cattle feeding is potential to reduce feed cost. Pineapple waste can be used as feed and as meat tenderizer. However, many believes that feeding pineapple waste to cattle distract beef quality. This study was aimed at assessing meat sensory quality of Brahman Cross cattle fed pineapple waste as fiber source. Six Brahman Cross (BX) cattle aged 2.5-3 years were used. The cattle were fattened for 120 days. Three cattle was fed rations containing concentrate and pineapple waste silage and the remaining cattle was fed rations containing concentrate and corn leaf silage. In the end of the study period, the animals were slaughtered and meat was cut based on the commercial slaughtering standard. Meat samples of Longissimus dorsi muscles were taken. Beef sample aging was conducted at 0ºC for 3 months. Measurements of beef characteristics were taken monthly. A completely randomized design was used. Data were subjected to a Kruskal Wallis test and meat physical characteristics were analysed by repetaed measurement analysis of variance. The parameters observed comprised pH values, tenderness, cooking loss, water holding capacity, meat colors (L*, a*, b* value), organoleptic test hedonic and hedonic quality (aroma, tenderness, color, and mucus). The results showed that the pineapple waste did not have significant influences on meat physical characteristics observed, except meat color a* values at two month aging, meat color L* value at three month aging. It was concluded that pineapple was could be used as a fiber source in beef cattle fattening with no negative effect on meat quality.